광평수(廣坪數) 토지 평가방법에 대한 고찰 - 임재만; Jae Man Lim (감정평가학 논집, 2015)
광평수 토지는 인근의 최유효이용 중인 표준적 규모의 토지에 비해 열등하다고 인식되어 왔다. 최근들어 도시토지개발프로젝트에서 쇼핑센터, 비즈니스 파크, 복합용도 개발 등을 목적으로 광평수 토지에 대한 수요가 증대하고 있다. 관련 선행연구는 토지면적과 가치의 관계에서 토지면적 증가에 따라 일정한 변곡점까지는 토지가격이 체증적으로 상승하는 볼록성(convexity)을 보이지만 변곡점 이후에는 토지가격이 체감적으로 상승하는 오목성(concaveness)을 보인다고 주장한다. 이러한 관계는 소규모 토지는 합병가능성이, 대규모 토지는 구획가능성이 존재하기 때문이다. 이 논문에서는 광평수 토지에 대한 시장지역분석, 최유효이용의 판단, 가치평가방법에 대한 이론을 검토했다. 광평수 토지는 토지의 구획화 또는 특이한 용도로 단독 이용 방법으로 사용할 수 있다. 감정평가사는 광평수 토지를 평가하기 위해 토지개발사업 또는 부동산개발사업과 관련된 많은 가정과 조건이 부가된 개발법을 적용할 수 있다. It has been recognized that larger land parcels are inferior to standard size land allocating highest and best use(HBU). Recently, urban land development projects need larger lots for shopping center, business park, multi-purpose complex buildings. So larger parcels might have more advantages than small or standard size lots. Previous studies show that there is convex(land value increasing at increasing rate) and concave(land value increasing at decreasing rate) relationship between land size and value because of plottage and plattage possibilities. I review the appraisal theories on market area analysis, HBU determination, land valuation methods of larger land parcels. Larger land parcels can be used through by land subdivision or single use. Appraisers can apply development method in order to value the larger land parcels under many assumptions and conditions of the projects.